Assessing Gene Expression Related to Cisplatin Resistance in Human Oral Squamous Cell Carcinoma Cell Lines - Hyeong Sim Choi; Young-Kyun Kim; Pil-Young Yun (MDPI AG, 2022)
Cisplatin-based chemotherapy has been effectively used to treat oral cancer, but treatment often fails owing to the development of drug resistance. However, the important gene expression alterations associated with these resistances remain unclear. In this study, we aimed to identify the gene expressions related to cisplatin resistance in oral squamous cell carcinoma (OSCC) cell lines. RNA samples were obtained from three cisplatin-resistant (YD-8/CIS, YD-9/CIS, and YD-38/CIS) and -sensitive (YD-8, YD-9, and YD-38) cell lines. Global gene expression was analyzed using RNA sequencing (RNA-Seq). Differentially expressed genes were determined. Based on the gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, functional enrichment and signaling pathways analyses were performed. Candidate genes selected from RNA-Seq analysis were validated by quantitative real-time polymerase chain reaction (qRT-PCR) analysis. The YD-8/CIS and YD-9/CIS samples had very similar expression patterns. qRT-PCR analysis was performed on selected genes commonly expressed between the two samples. The expression levels of 11 genes were changed in cisplatin-resistant samples compared with their parental samples; several of these genes were related to cell adhesion molecules and proteoglycans in cancer pathways. Our data provide candidate genes associated with cisplatin resistance in OSCC, but further study is required to determine which genes have an important role. Nevertheless, these results may provide new ideas to improve the clinical therapeutic outcomes of OSCC.